FINANCING ISLAMIC FINANCIER INVESTMENT PROJECTS (Conferencea, 2023)
According to the report of the Council of International Financial Services, "In 2022, the volume of financing of investment projects in the global financier association will be 3.25 trillion. Established the US Cabinet. However, due to problems such as the decrease in inflation, the increase in the price of oil and raw materials, and geopolitical uncertainty, the volume of financing of investments in the global financial institution increased by 11.3 percent in 2021 and 6.2 percent in 2022. This system of financing the investment project is developing due to the aspects such as the proportional distribution of the level of poverty, the fairness of the income level, and the importance of the economic development to the social development.Starting from the beginning of the financing activity of the Iclom financier association, it can be said that the importance of the waqf fund is important in the implementation of the main project and the financial support of the main business activity. According to the results of the conducted research, it is reported that the activities of waqf muaccacalapa are widely found in the Muslim society of the region. In this case, the waqf fund was a key link in the higher system of government in a Muslim country. In this way, the government has implemented an initiative to reduce the financial burden on the state treasury, to finance other economic and financial activities.